Dwi Ratnaningsih BIAYA OPERASIONAL KENDARAAN DI PERSIMPANGAN JALAN HASYIM ASHARI – JALAN ARIEF MARGONO KOTA MALANG - Dwi Ratnaningsih; Susapto Susapto; Benediktus Narindra (Jurnal Qua Teknika, 2020)
Hashim Asyari Street Intersection - Arief Margono Street Malang City is one of the intersections in Malang City with high traffic volume. Based on observations in the field during peak hours (peak hour) at the intersection often there is a long queue due to the amount of traffic volume exceeds the capacity of the intersection. The impact of a long queue one of which is the increase in vehicle operating costs. This study aims to calculate the vehicle operating costs in the existing conditions. The data needed for analysis includes intersection geometric data, traffic volume, side barriers, speed, population of Malang, etc. Analysis of intersection performance based on the 1997 MKJI and operational costs using the BOK calculation method issued by Pacific Consultant International. Based on the analysis results obtained the performance of the intersection in the existing conditions are in class F. Vehicle operating costs at the time of the condition amounted to Rp 3,521,026 / hour.